2015
DOI: 10.1055/s-0035-1555776
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Threshold by Mathematical Model in Healthy and Post-Myocardial Infarction Men

Abstract: The aim of this study was to determine the anaerobic threshold (AT) in a population of healthy and post-myocardial infarction men by applying Hinkley's mathematical method and comparing its performance to the ventilatory visual method. This mathematical model, in lieu of observer-dependent visual determination, can produce more reliable results due to the uniformity of the procedure. 17 middle-aged men (55±3 years) were studied in 2 groups: 9 healthy men (54±2 years); and 8 men with previous myocardial infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The inclusion of a relatively large sample of presurgical AAA subjects overcomes one of the limitations in previous studies, that is, comparing different methods of determining VT among young healthy subjects. 11,[20][21][22][33][34][35][36][37] In general, our findings are consistent with previous reports showing fairly good agreement between different methods of determining VT. 11,19,22,[33][34][35]37 In this regard, several studies have shown moderately high correlation (r = 0.59-0.98) between computed mathematical models, and visual readings of the VT, lactate responses, or both. 11,19,22,[33][34][35]37 Nevertheless, these relatively high associations between methods are contrasted by several other studies reporting poor agreement.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The inclusion of a relatively large sample of presurgical AAA subjects overcomes one of the limitations in previous studies, that is, comparing different methods of determining VT among young healthy subjects. 11,[20][21][22][33][34][35][36][37] In general, our findings are consistent with previous reports showing fairly good agreement between different methods of determining VT. 11,19,22,[33][34][35]37 In this regard, several studies have shown moderately high correlation (r = 0.59-0.98) between computed mathematical models, and visual readings of the VT, lactate responses, or both. 11,19,22,[33][34][35]37 Nevertheless, these relatively high associations between methods are contrasted by several other studies reporting poor agreement.…”
Section: Discussionsupporting
confidence: 92%
“…22,33,34,36,37 ) observed using a cycle ergometer test among surgical candidates with high perioperative risk. This reflects the 10-25% higher values typical for treadmill testing vs the cycle ergometer.…”
Section: áMinmentioning
confidence: 99%
“…Symptom-limited CPET was performed on a treadmill (Master ATL, Inbramed, Porto Alegre, Rio Grande do Sul, Brazil). e ramping protocol was based on a previous study [18] (respecting the maximal walking velocity without running) with objective to identifying the value of ventilatory anaerobic threshold (VAT) [2,[25][26][27][28] of each participant.…”
Section: Cpetmentioning
confidence: 99%
“…Data were analyzed after smoothed by moving averages of eight respiratory cycles [25]. Using the ventilatory method, three independent evaluators determined the VAT [25,27,28]. Oxygen uptake (VO 2 ), VCO 2 (carbon dioxide production), and respiratory exchange ratio (RER) (defined as the ratio between VCO 2 and VO 2 ) of the peak were expressed as the highest averaged values observed during the last 30 s of exercise [18,19].…”
Section: Cpetmentioning
confidence: 99%
“…In this regard, detection of maximal oxygen consumption (VO 2max ) and aerobic and anaerobic thresholds are the main determinants of aerobic fitness in athletes, 2 , 3 subjects with impaired health, 4 , 5 and healthy individuals. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%